Comparative study to evaluate the success rate of manual vaccum aspiration and Medical abortion in termination the first trimester pregnancy - Bhardwaj, Malini; Bhargava, Sumit (International Journal of Medical Research and Review, 2015)
Objectives: This study was undertaken to evaluate the success rate of manual vaccume aspiration in termination the first trimester pregnancy, study the merits and demerits of the method and compare it with other method i.e. medical abortion by misoprostol and mifepristone in first trimester MTP. Methodology: In a prospective randomized controlled study, participants were divided in two groups: Study group of 30 patients of 6-12 weeks gestational age subjected to MTP by manual vacuum aspiration. Another group consisted of 30 patients of 6-8- weeks gestational age who were subjected to MTP by medical method using mifepristone and misoprostol. Result: Present study consist of 30 cases of medical termination of pregnancy in Ist trimester carried out by (manual vaccum aspiration) MVA. A comparison of observation and results was made with another group of 30 patients who had undergone pregnancy termination in Ist trimester using mifepristone and misoprostol. In 6-8 weeks pregnancies incidence of complete abortion was 100% In 10 weeks complete termination was done in 8 patient’s only 1 patient had incomplete termination. In medical abortion also results show that in up to 6 week pregnancy 3(12%) patient had incomplete expulsion, in up to 8 week 11(20%) patient had incomplete expulsion In present study over all success rate with MVA was 93.33% whereas with medical abortion success rate is found to be 86.67%. Conclusion: It is concluded from present study that Manual Vaccum Aspiration is safe, simple and easy procedure with minimal need of anesthesia and analgesia. It is very good option in low resource settings.